Fiscal Multipliers and the State of the Economy - Baum, Anja.; Poplawski Ribeiro, Marcos; Weber, Anke. (Washington, D.C. : International Monetary Fund, 2012)
Only a few empirical studies have analyzed the relationship between fiscal multipliers and the underlying state of the economy. This paper investigates this link on a country-by-country basis for the G7 economies (excluding Italy). Our results show that fiscal multipliers differ across countries, calling for a tailored use of fiscal policy. Moreover, the position in the business cycle affects the impact of fiscal policy on output: on average, government spending, and revenue multipliers tend to be larger in downturns than in expansions. This asymmetry has implications for the choice between an upfront fiscal adjustment versus a more gradual approach.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet